Copepod phylogenomics supports Canuelloida as a valid order separate from Harpacticoida - James P. Bernot; Sahar Khodami; Jens Boyen; Marleen De Troch; Geoffrey A. Boxshall; Pedro Martínez Arbizu (Molecular Phylogenetics and Evolution, 2025)

A new genus of Herpyllobiidae (Copepoda: Cyclopoida) from a deep-living annelid (Polychaeta: Sigalionidae) - Eduardo Suárez-Morales; Christopher Cruz-Gómez; Geoffrey A. Boxshall (Systematic Parasitology, 2024)

Exploring evolutionary trends within the Pennellidae (Copepoda: Siphonostomatoida) using molecular data - Nanami Yumura; Kenta Adachi; Masato Nitta; Yusuke Kondo; Sota Komeda; Kaori Wakabayashi; Jun Fukuchi; Geoffrey A. Boxshall; Susumu Ohtsuka (Systematic Parasitology, 2022)

Sea lice (Copepoda: Caligidae) from South Africa, with descriptions of two new species of Caligus - Polly M. Hayes; Kevin W. Christison; David B. Vaughan; Nico J. Smit; Geoffrey A. Boxshall (Systematic Parasitology, 2021)
Thirteen species of sea lice (family Caligidae) are reported from a range of elasmobranch and actinopterygian fishes caught off South Africa or obtained from public aquaria in South Africa. Two new species of Caligus Müller, 1785 are described: C. linearis n. sp. from Pomatomus saltatrix (Linnaeus) and C. tumulus n. sp. from Chrysoblephus cristiceps (Valenciennes). A supplementary description is provided for both sexes of Caligus tetrodontis Barnard, 1948 taken from Amblyrhynchotes honckenii (Bloch) and previous records of this parasite from South African fishes are critically reviewed. It is concluded that Caligus material from Arothron hispidus Linnaeus was previously misidentified as C. tetrodontis and is in urgent need of re-examination. Morphological and molecular observations on Caligus furcisetifer Redkar, Rangnekar & Murti, 1949 indicate that this copepod is phenotypically and genetically identical to Lepeophtheirus natalensis Kensley & Grindley, 1973, and the latter becomes a junior subjective synonym of C. furcisetifer . We include new geographical distribution records for Caligus longipedis Bassett-Smith, 1898, C. rufimaculatus Wilson, 1905 and Lepeophtheirus spinifer Kirtisinghe, 1937, extending into South African waters, as well as both new distribution and host records for Alebion gracilis Wilson, 1905, Caligus dakari van Beneden, 1892 and Lepeophtheirus acutus Heegaard, 1943. The molecular analysis confirmed the monophyly of the genus Caligus. The South African species of Caligus did not cluster together, but the two included South African species of Lepeophtheirus were recovered as sister taxa.

Lepeophtheirus azoricus n. sp. (Copepoda: Caligidae) parasitic on dusky grouper, Epinephelus marginatus, from Atlantic waters off the Azores, Portugal - Argun Akif Özak; Alfredo M. V. Rodrigues; Nina S. S. Vieira; Rui M. G. Rosa; Alper Yanar; Erkin Koyuncu; Geoffrey A. Boxshall (Marine Biodiversity, 2018)

Redescription of Tripaphylus musteli (van Beneden, 1851) (Copepoda: Sphyriidae) and the relegation of Paeon Wilson, 1919 to synonymy with Tripaphylus Richiardi in Anonymous, 1878 - George W. Benz; Geoffrey A. Boxshall (Systematic Parasitology, 2017)

A new species of Pseudopandarus Kirtisinghe, 1950 (Copepoda: Siphonostomatoida: Pandaridae) from sharks of the genus Squalus L. in New Caledonian waters - James P. Bernot; Geoffrey A. Boxshall (Systematic Parasitology, 2017)

Caligus solea n. sp. (Copepoda: Caligidae) parasitic on the common sole Solea solea (Linnaeus) from the north-eastern Mediterranean off the Turkish coast - İbrahim Demirkale; Argun A. Özak; Alper Yanar; Geoffrey Allan Boxshall (Systematic Parasitology, 2014)

A new species of Sabellacheres M. Sars, 1862 (Copepoda: Gastrodelphyidae) from a deep-water benthic polychaete in Antarctic waters, with a key to the species of the genus - Eduardo Suárez-Morales; Geoffrey A. Boxshall (Systematic Parasitology, 2012)

Sagum posteli Delamare-Deboutteville & Nunes-Ruivo, 1954 (Copepoda: Siphonostomatoida: Lernanthropidae) parasitic on Epinephelus aeneus (Geoffroy Saint-Hilaire) in Turkish waters, with a key to the species of Sagum Wilson, 1913 - Erol Toksen; Geoffrey A. Boxshall; Sıdıka Altinozek (Systematic Parasitology, 2012)

An all-conquering ecological journey: from the sea, calanoid copepods mastered brackish, fresh, and athalassic saline waters - Ian A. E. Bayly; Geoffrey A. Boxshall (Hydrobiologia, 2009)

Preface - Sami Souissi; Geoffrey A. Boxshall (Hydrobiologia, 2009)

A new species of Anuretes Heller, 1865 (Copepoda: Caligidae) from the yellowbanded sweetlips Plectorhinchus lineatus (Haemulidae) off New Caledonia - B. A. Venmathi Maran; Susumu Ohtsuka; Geoffrey A. Boxshall (Systematic Parasitology, 2008)

A new genus and species of nicothoid copepod (Crustacea: Copepoda: Siphonostomatoida) parasitic on the mysid Siriella okadai Ii from off Japan - Susumu Ohtsuka; Geoffrey A. Boxshall; Shinsuke Harada (Systematic Parasitology, 2005)

Parasitic copepods (Copepoda: Siphonostomatoida) from deep-sea and mid-water fishes - Geoffrey A. Boxshall (Systematic Parasitology, 2000)

Description of a new Nipergasilus species (Family: Ergasilidae) from the gills of grey mullet - Hoda H. El-Rashidy; Geoffrey A. Boxshall (Hydrobiologia, 2000)

Two new species of Paracyclops (Copepoda: Cyclopoida, Cyclopidae) from Africa - Süphan Karaytug; Danielle Defaye; Geoffrey A. Boxshall (Hydrobiologia, 1998)